1990
DOI: 10.1017/s0890037x00025379
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Additives on Efficacy, Uptake, and Translocation of Chlorimuron Ethyl Ester

Abstract: Effects of a 28% N solution containing urea and ammonium nitrate (28% UAN) and a nonionic surfactant on efficacy, uptake, and translocation of chlorimuron ethyl ester in soybean and broadleaf weeds were investigated. Chlorimuron applied postemergence at 8.8 and 13 g ai/ha with either nonionic surfactant at 0.25% (v/v), 28% UAN at 9.4 L/ha, or nonionic surfactant plus 28% UAN controlled weeds better than without additives. Chlorimuron with nonionic surfactant and with 28% UAN controlled weeds similarly but with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 25 publications
5
21
1
Order By: Relevance
“…More than 500 different mixtures are used in Europe each year (4). A person no longer can consider all mixture possibilities and complete the complex analyses needed to use herbicide mixtures efficiently (3,4,9).…”
Section: Introductionmentioning
confidence: 99%
“…More than 500 different mixtures are used in Europe each year (4). A person no longer can consider all mixture possibilities and complete the complex analyses needed to use herbicide mixtures efficiently (3,4,9).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have observed that adjuvant efficacy is dependent on the herbicide being applied and the characteristics of the target weed species [61][62][63]. For example, MSO increase foliar absorption and efficacy of many herbicides, including primisulfuron, rimsulfuron, imazethapyr, quinclorac, and several graminicides for grass weed control [21,[64][65][66].…”
Section: Positive Interaction Between Herbicide Efficacy and Adjuvantsmentioning
confidence: 99%
“…The addition of AMS or UAN to the spray solution can enhance herbicide effectiveness by further increasing herbicide absorption [26,72] which gives better result up to 12%--13.5% than use of herbicide alone [73]. For instance, thifensulfuron absorption into velvetleaf (Abutilon theophrasti Medicus) was increased from 4% to 45% when 28% UAN was added to the spray solution [61,74,75]. Addition of AMS and potassium phosphate to the spray solutions of MSMA and dalapon enhanced control of Sorghum halepense (L.) Pers.…”
Section: Positive Interaction Between Herbicide Efficacy and Adjuvantsmentioning
confidence: 99%
“…However, saflufenacil treatments with DAS did not show any differences in control of common lambsquarters compared to saflufenacil in deionized water without DAS. Several studies have suggested that DAS increases the foliar absorption of herbicides, which consequently increases efficacy (6,7,9). Moreover, according to the label of saflufenacil, this product must be applied with DAS and methylated seed oil (2).…”
Section: Influence Of Water Hardness On Saflufenacil Efficacymentioning
confidence: 99%